Avaliação da qualidade da atenção pré-natal oferecida às gestantes no município de Fortaleza (CE) - Ricarte, Fernanda Maria Cunha (2011)
Introduction: Prenatal care has high priority in public health policy in Brazil, due to it is strong influence on rates of maternal and infant morbidity and mortality. Evaluation processes of the quality of care for pregnant women are important tools for optimizing the impact of health services on maternal and fetal health. The goal of the study was to evaluate the quality of prenatal care offered to pregnant women in Fortaleza (CE), using parameters established by the Ministry of health, aiming to contribute to the improvement of care for women in pregnancy and childbirth. Methodology: The cross-sectional study was based on the V Study on Maternal and Child Health of CearÃ¡ (PESMIC), a population survey carried out in a sample of women of reproductive age living in Fortaleza. From the 2.553 surveyed women, 195 reported a birth in the previous 12 months, being the target of the analysis. The quality of care was a evaluated in three levels of complexity: Level 1, the onset and frequency of consultations; Level 2, Level 1 plus the completion of laboratory tests, and level 3, Levels 1 and 2, plus the achievement of clinical and obstetric procedures. The chi-square test was used to evaluate the statistical significance (Î±=0,05) of associations between characteristics of pregnant women and prenatal care. Results: Pregnant adolescents were associated with fewer consultations (p=0,057) and HIV testing (p=0,014), as compared with adults. Pregnant women without a partner had a later start of the prenatal care (p=0,004) and fewer consultations (p=0,032), than those living with a partner. Pregnant women with years of schooling up to 8 years were associated with fewer visits (p=0,024) and lower guidance relating to breast feeding (p=0,001), compared to those with more than 8 years of schooling. Family income of up to 2 minimum wages were associated to a later beginning of the prenatal care (p=0,018) and lower referral to delivery care facilities (p=0,018), as compared to those with income above 2 minimum wages. Pregnant women who had the SUS as a health care provider, were associated with an late pre natal care (p=0,001), fewer consultations (p=0,002), less breastfeeding advice (p=0,029), and lower referral to delivery care facilities (p=0,017) as compared to those who had health insurance. The assessment of the quality of care found that only 63% of pregnant women started and managed to hold consultations at the appropriate time (Level 1). When this parameter was added to the performing of basic laboratory tests (Level 2), the percentage was only slightly reduced, to 55%. However, when these two levels were considered in conjunction with Level 3 (clinical and obstetric procedures performed by professionals) the percentage of adequacy has dropped dramatically, reaching only 3,6 %. Conclusion: Despite it is high coverage, prenatal care in Fortaleza should be reconsidered qualitatively. It is recommended a broad discussion of the results of this assessment with managers, health professionals and community, as well as the organization of a training program for improving the technical quality of the care provided by such professionals. â€ƒ